2021
DOI: 10.1016/j.ijid.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Statins reduce mortality in patients with COVID-19: an updated meta-analysis of 147 824 patients

Abstract: Objectives There is conflicting evidence about the utility of statins use on clinical outcomes in patients with coronavirus disease 2019 (COVID-19). We performed a systematic review and meta-analysis to examine the effect of statins use on mortality in COVID-19 patients. Methods We searched electronic databases from inception to March 3, 2021. We pooled unadjusted and adjusted effect estimates with their 95% confidence intervals (95% CI) using random-effects models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 38 publications
2
35
0
2
Order By: Relevance
“…Statins have been reported to have pleiotropic and protective effects on endothelial cells [ 205 ]. A meta-analysis of 25 cohort studies involving 147,824 participants reported that the use of statin was associated with a lower risk of mortality in COVID-19 patients [ 206 ]. Randomized clinical trials are under way to further investigate the impact of statin use on clinical outcomes in COVID-19.…”
Section: Therapeutic Approaches Targeting Thromboinflammation and Endothelial Injury In Covid-19mentioning
confidence: 99%
“…Statins have been reported to have pleiotropic and protective effects on endothelial cells [ 205 ]. A meta-analysis of 25 cohort studies involving 147,824 participants reported that the use of statin was associated with a lower risk of mortality in COVID-19 patients [ 206 ]. Randomized clinical trials are under way to further investigate the impact of statin use on clinical outcomes in COVID-19.…”
Section: Therapeutic Approaches Targeting Thromboinflammation and Endothelial Injury In Covid-19mentioning
confidence: 99%
“…In several other retrospective studies, the benefits of antecedent use of statins before admission were equivocal [8] , [9] , [10] , [11] , [12] , [13] , [14] . Moreover, despite the favorable results of using statin on survival in recent meta-analyses, the studies exposures included in these meta-analyses were heterogenous: some studied the effect of antecedent use of statins while others studied in-hospital use of statins [15] , [16] , [17] . However, it remains unclear whether statin use during or prior to hospitalization or continuous use of statins from the period antecedent to hospital admission through hospitalization period is beneficial to COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Atorvastatin was co-prescribed 23.21% of the time and Simvastatin 9.49% of the time. Due to these high prescription rates and reports describing an association between statin use and reduced mortality from COVID-19 14,15 we included statins in Model 2.…”
Section: Resultsmentioning
confidence: 99%